2020
DOI: 10.29245/2578-2959/2019/1.1192
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Parent-Reported Anxiety and Emotional Functioning in Children with Developmental Challenges After Participation in the Brain Balance® Program

Abstract: Children with developmental or learning challenges often have cooccurring difficulties in emotional functioning. There is a longstanding need to identify effective nonpharmacologic treatments to address these emotional difficulties. However, few studies have examined training programs that are multimodal in nature and their effects specifically on mental well-being. The purpose of this study is to estimate the impact of an integrative multimodal training program (Brain Balance ® ) on mental well-being in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
0
7
0
3
Order By: Relevance
“…El valor de las intervenciones escolares que adoptan enfoques integradores más amplios ha quedado en gran medida sin explorar. La eficacia del programa Brain Balance en el propio centro se ha demostrado previamente en grandes muestras de niños y adolescentes con problemas de desarrollo y de atención que mostraron mejoras significativas en el rendimiento cognitivo (Jackson & Wild, 2021), la atención (Jackson & Jordan, 2022;Teicher et al, 2023) y el bienestar mental percibido por los padres (Jackson & Robertson, 2020). En particular, los niños y adolescentes (de 4 a 17 años) que participaron en el programa Brain Balance durante tres meses experimentaron mejoras significativas en el rendimiento general en pruebas de memoria, razonamiento, capacidad verbal y concentración (Jackson & Wild, 2021) y experimentaron, en general, una disminución de los síntomas del trastorno por déficit de atención con hiperactividad (TDAH) en las puntuaciones calificadas por los padres en la Escala de TDA de Brown ® (Jackson & Jordan, 2022).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…El valor de las intervenciones escolares que adoptan enfoques integradores más amplios ha quedado en gran medida sin explorar. La eficacia del programa Brain Balance en el propio centro se ha demostrado previamente en grandes muestras de niños y adolescentes con problemas de desarrollo y de atención que mostraron mejoras significativas en el rendimiento cognitivo (Jackson & Wild, 2021), la atención (Jackson & Jordan, 2022;Teicher et al, 2023) y el bienestar mental percibido por los padres (Jackson & Robertson, 2020). En particular, los niños y adolescentes (de 4 a 17 años) que participaron en el programa Brain Balance durante tres meses experimentaron mejoras significativas en el rendimiento general en pruebas de memoria, razonamiento, capacidad verbal y concentración (Jackson & Wild, 2021) y experimentaron, en general, una disminución de los síntomas del trastorno por déficit de atención con hiperactividad (TDAH) en las puntuaciones calificadas por los padres en la Escala de TDA de Brown ® (Jackson & Jordan, 2022).…”
Section: Discussionunclassified
“…The Brain Balance programme, a multimodal childhood training programme, has previously been demonstrated to improve cognitive performance and mental well-being in a centre-based setting (Jackson & Jordan, 2022; Jackson & Robertson, 2020; Jackson & Wild, 2021) but had not yet been implemented or examined in a school setting. In the present study, we showed that students (aged 5–15 years) with developmental challenges who participated in the Brain Balance programme in a school setting displayed improvements in: (1) primitive reflex integration and sensorimotor skills; and (2) teacher-rated behaviours as measured by VADTRS scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Brain Balance program consisted of three incenter sessions per week (for 3 months), with each session lasting 1 hour (45 minutes of sensorimotor stimulation and a 15-minute academic component focused on literacy and listening activities), along with other multimodal activities targeting the areas described in the list below. This training program protocol has previously been described in detail in Jackson & Robertson [34]. The program stations consisted of the following key pieces:…”
Section: Training Programmentioning
confidence: 99%